Pathogens, endosymbionts, and blood-meal sources of host-seeking ticks in the fast-changing Maasai Mara wildlife ecosystem - Oundo, J.W.; Villinger, J.; Jeneby, M.; Ong’amo, G.; Otiende, M.Y.; Makhulu, E.E.; Musa, A.A.; Ouso, D.O.; Wambua, Lillian (Public Library of Science, 2020)
The role of questing ticks in the epidemiology of tick-borne diseases in Kenya’s Maasai Mara National Reserve (MMNR), an ecosystem with intensified human-wildlife-livestock interactions, remains poorly understood. We surveyed the diversity of questing ticks, their blood-meal hosts, and tick-borne pathogens to understand potential effects on human and livestock health. By flagging and hand-picking from vegetation in 25 localities, we collected 1,465 host-seeking ticks, mostly Rhipicephalus and Amblyomma species identified by morphology and molecular analysis. We used PCR with high-resolution melting (HRM) analysis and sequencing to identify Anaplasma, Babesia, Coxiella, Ehrlichia, Rickettsia, and Theileria pathogens and blood-meal remnants in 231 tick pools. We detected blood-meals from humans, wildebeest, and African buffalo in Rh. appendiculatus, goat in Rh. evertsi, sheep in Am. gemma, and cattle in Am. variegatum. Rickettsia africae was detected in Am. gemma (MIR = 3.10) that had fed on sheep and in Am. variegatum (MIR = 250) that had fed on cattle. We found Rickettsia spp. in Am. gemma (MIR = 9.29) and Rh. evertsi (MIR = 200), Anaplasma ovis in Rh. appendiculatus (MIR = 0.89) and Rh. evertsi (MIR = 200), Anaplasma bovis in Rh. appendiculatus (MIR = 0.89), and Theileria parva in Rh. appendiculatus (MIR = 24). No Babesia, Ehrlichia, or Coxiella pathogens were detected. Unexpectedly, species-specific Coxiella sp. endosymbionts were detected in all tick genera (174/231 pools), which may affect tick physiology and vector competence. These findings show that ticks from the MMNR are infected with zoonotic R. africae and unclassified Rickettsia spp., demonstrating risk of African tick-bite fever and other spotted-fever group rickettsioses to locals and visitors. The protozoan pathogens identified may also pose risk to livestock production. The diverse vertebrate blood-meals of questing ticks in this ecosystem including humans, wildlife, and domestic animals, may amplify transmission of tick-borne zoonoses and livestock diseases.